Students’ teacher-dependency and passiveness in online learning during COVID-19 pandemic - Teguh Ariebowo; Evi Puspitasari (Intelektual Pustaka Media Utama, 2022)
Online learning during COVID-19 pandemic has made teacher and students even parents busy in adapting the change. Many issues rose regarding the implementation of online learning. One of the issues is the student's teacher dependency in learning. Along with this problem, students tend to be passive in online learning. This research was conducted in a higer education context. Quantitative survey research was conducted to 656 sophomore students and 10 teachers in a college of aerospace technology in Yogyakarta, Indonesia. Along with the questionnaire, an interview was held to gain the qualitative data to support the quantitive data. As the result, students tend to rely on their teachers and passive in learning.